Interaction Between Low Molecular Weight Chitosan and Some Types of Drugs and Insulin - Al-Sou'od, Khaldoun (Asian Journal of Chemistry, 2012)
The complexation between ibuprofen, declofenac and insulin with the low molecular weight chitosan was studied using molecular modeling method. Molecular mechanics calculations were used to have insight into interaction stoichiometry between chitosan and ibuprofen. The results of molecular mechanics showed that the complexation of ibuprofen with low molecular weight chitosan involves ionic interaction between the ammonium group of low molecular weight chitosan and the carboxylate anion of ibuprofen. Chitosan was built in two different forms. The long one practically can be obtained from diluted solutions while the short one are from concentrated solutions. The modeling show that the chitosan-ibuprofen complex is best prepared from diluted solutions of the chitosan polymer. Human insulin is also build using a hyperchem software. It is a rather small protein, with a molecular weight of about 6000 Daltons. It is composed of two chains (A and B) held together by disulphide bonds. The interaction between human insulin and low molecular weight chitosan was studied using molecular mechanics calculations.